The role of video game consumption habits in the relationship between gender and attitudes towards violence among adolescents - Julia Sánchez-García; Pablo Usán Supervía (Scientific Reports)
Abstract Research in adolescent population is key to understand the behaviors and attitudes that can modulate their personal and social development. This research examines the mediating role of video game consumption habits (interference with other activities, interference with academic activities, degree of attraction and degree of restlessness) in the relationship between gender and attitudes towards violence among adolescents. Moreover, the moderating role of frustration tolerance in the influence of mediation effects is analyzed. The main contribution of the study is the consideration of different indicators of consumption habits that explain gender differences in attitudes towards violence among adolescents. The study comprised a total of 877 secondary school students aged 12–18 male (N = 465) and female (N = 412) adolescents. The empirical estimation uses Hayes’ moderated mediation framework. The results showed that the indirect effect of gender attitudes of violence among adolescents through video game consumption habits was conditioned by the level of frustration tolerance. Specifically, when frustration tolerance is high, being female is associated with a reduction in the interference that video games produce in activities, which in turn reduces their positive attitudes towards violence. The promotion of pedagogical strategies and guidelines based on frustration tolerance in a younger population could be relevant to rejecting positive attitudes towards violence.